2016
DOI: 10.3892/ol.2016.5211
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP9, SERPINE1 and miR-134 as prognostic factors in esophageal cancer

Abstract: Abstract. Esophageal cancer (EC) is a malignant tumor with a typically poor prognosis for patients. It is well known that certain microRNA (miRNA/miR) genes can regulate other genes responsible for carcinogenesis. In the present study, a group of these genes (miR-21, miR-134, miR-205 and miR-495) and genes connected with cancer-related pathways (MET, MMP9, PDGFA and SERPINE1) were chosen for analysis in order to find a potential correlation between their expression and the clinicopathological factors of EC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“… 20 Klimczak-Bitner et al demonstrated that the expression of SERPINE1 may be one of the key prognostic genes in esophageal cancer. 21 Pavón et al reported that overexpression of SERPINE1 enhances tumor cell migration and invasion. 22 We found that SERPINE1 was significantly upregulated in gastric tissues and SERPINE1 high expression associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Klimczak-Bitner et al demonstrated that the expression of SERPINE1 may be one of the key prognostic genes in esophageal cancer. 21 Pavón et al reported that overexpression of SERPINE1 enhances tumor cell migration and invasion. 22 We found that SERPINE1 was significantly upregulated in gastric tissues and SERPINE1 high expression associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the miRNA profile of tissues exhibits characteristic changes in certain types of tumors [19,20]. A number of miRNAs have been shown to participate in tumor progression, invasion, and metastasis, including miR-134 [21], miR-145 [22], miR-625 [23], and miR1294 [24]. However, due to clinical heterogeneity, sample insufficiency, and use of various data processing methods, there is inconsistency in the results of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study suggested that increased MMP9 expression was associated with gastric cancer cell invasion. 41 In addition, MMP9 activity has been reported to be correlated with prognosis of other cancers, including cancers of the lung, 42 colorectum, 43 esophagus, 44 and breast. 45 Importantly, transcript levels of MMP9 were also observed to be increased in melanoma tumors, compared with that of melanocyte controls.…”
Section: Discussionmentioning
confidence: 99%